Baseband version of the bat-inspired spectrogram correlation and transformation receiver - Georgiev, Krasin (Cranfield University, 2016)
Poster presentation at the 2016 Defence and Security Doctoral Symposium. Echolocating bats have evolved an excellent ability to detect, resolve and discriminate targets in highly challenging environments. They have had more than 50 million years of evolution to optimise their echolocation system and behavioural experiments have shown their exceptional ability to detect and classify targets even in highly cluttered surroundings. Behavioural experiments have demonstrated that bats are able to resolve closely located scatterers: •a two-point resolution of 2÷10 μs with waveforms of a bandwidth of 85 kHz (Eptesicus fuscus) • discriminate between two phantom target echoes separated by a time-delay of about 1  μs with waveforms of a bandwidth of up to 100 kHz (Megaderma lyra) •higher range resolution performance with respect to the conventional matched filter. The way bats process target echoes is different from the standard processing techniques used in radar and sonar, and there may be lessons to learn by investigating differences and similarities. The Spectrogram Correlation And Transformation receiver (SCAT) is an existing model of the bat auditory system that takes into account the physiology and underlying neural organisation in bats that emit chirped signals. The aims of this work are: •develop a baseband receiver equivalent to the SCAT to    - allow the application of biologically inspired signal processing to radar baseband signals  - enable further theoretical analysis of the key concepts, advantages and limitations of the “bat signal processing” •carry out simulations and experimen ts to investigate differences and similarities between the output (the frequency interference pattern for two closely located scatterers) of the original SCAT and that of the proposed baseband version.
Keywords: 'Echo location'; 'SCAT'; 'Radar'; 'DSDS16 poster'; 'DSDS16'; 'Antennas and Propagation'